Theoretical Study to Select Wind Turbines and Energy Production for the Entire Area in Iraq - Hamid, Saib; Aljanabi, Sabah; Mohammed, Tawfeeq; H. Al-Moameri, Harith; Hussam, Wisam (Journal of Engineering and Sustainable Development, 2025)
The majority of electrical power generation systems in Iraq are gas turbine stations that cause many economic and environmental problems since they are based on fossil fuel sources. Renewable energy, specifically wind, can be a solution (besides solar energy) to produce clean energy. Throughout this work, specific wind turbines can be suggested within certain dimensions and hub heights to satisfy viable rated power for available wind density.  Many regions in Iraq, especially eastern and western regions, seem promising locations for installing wind turbines for electricity generation. The results showed that these locations have a power density between 700-1200 kWh/m2 annually at an elevation of 80 m as a critical height. The suggested horizontal axis turbine can offer rated power of up to 200 kW, reaching 350 kW in some locations, especially in Hay district and around. Other locations (southern and internal regions) can produce less power, and they are suitable for vertical axis turbines with rated power of 10-20 kW. However, some locations are not recommended for large-scale turbines due to the long time off-design period. Micro-turbines that produce 5 kW are suitable for the northern region of Iraq.